2017
DOI: 10.1080/1745039x.2017.1279712
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of leucine on redox status and mitochondrial-related gene abundance in the jejunum of intrauterine growth-retarded piglets during early weaning period

Abstract: The aim of this study was to investigate the effects of dietary supplementation with 0.35% l-leucine on redox status and gene abundance relating to mitochondrial biogenesis and function in the jejunum of intrauterine growth-retarded (IUGR) piglets during early weaning period. According to a 2 × 2 factorial arrangement, 16 IUGR and 16 normal body weight (NBW) piglets were fed a basal diet without l-leucine supplementation or a basal diet plus 0.35% l-leucine supplementation from the age of 14 to 35 d. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 42 publications
5
17
1
Order By: Relevance
“…Additionally, leucine supplementation has also been reported to increase ATP content and mitochondrial biogenesis in mice (Li, Xu, Lee, He, & Xie, 2012) and rats (Sato et al, 2018). Consistent with this, two recent studies found that leucine supplementation increased mitochondrial biogenesis by increasing mitochondrial-related genes expression in the jejunum of intrauterine growth-retarded (IUGR) piglets (Huang et al, 2017;Su et al, 2017). Our data indicated that 0.25% leucine supplementation improved the mitochondrial function.…”
Section: Mammalian Cells Have a Complex Network Of Antioxidant Enzymessupporting
confidence: 87%
See 4 more Smart Citations
“…Additionally, leucine supplementation has also been reported to increase ATP content and mitochondrial biogenesis in mice (Li, Xu, Lee, He, & Xie, 2012) and rats (Sato et al, 2018). Consistent with this, two recent studies found that leucine supplementation increased mitochondrial biogenesis by increasing mitochondrial-related genes expression in the jejunum of intrauterine growth-retarded (IUGR) piglets (Huang et al, 2017;Su et al, 2017). Our data indicated that 0.25% leucine supplementation improved the mitochondrial function.…”
Section: Mammalian Cells Have a Complex Network Of Antioxidant Enzymessupporting
confidence: 87%
“…In C2C12 cell model, leucine increased the ATP content and mitochondrial biogenesis (Du, Shen, Zhu, & Ford, 2007;Liang et al, 2014). Consistent with this, two recent studies found that leucine supplementation increased mitochondrial biogenesis by increasing mitochondrial-related genes expression in the jejunum of intrauterine growth-retarded (IUGR) piglets (Huang et al, 2017;Su et al, 2017). Consistent with this, two recent studies found that leucine supplementation increased mitochondrial biogenesis by increasing mitochondrial-related genes expression in the jejunum of intrauterine growth-retarded (IUGR) piglets (Huang et al, 2017;Su et al, 2017).…”
Section: Mammalian Cells Have a Complex Network Of Antioxidant Enzymessupporting
confidence: 53%
See 3 more Smart Citations